The potential of noodles incorporated with green seaweed Caulerpa lentillifera as a low‑glycaemic food - Nur Syakilla; Ramlah George @ Mohd. Rosli; Patricia Matanjun (Springer, 2025)
Caulerpa lentillifera has emerged as a promising source of bioactive compounds with some of the reported biological activities including anti-diabetic and anti-hyperglycaemic properties, which could be useful in managing and preventing diabetes mellitus. Our previous research fndings have demonstrated the sensorial acceptability of incorporating green seaweed C. lentillifera into noodles at a concentration level of 2.5% among consumers. Therefore, this study aims to evaluate the hypoglycaemic efects of noodles incorporated with 2.5% C. lentillifera powder (CLP), CLP2.5, alongside a control noodle, CLP0, and noodles with CLP5.0 by conducting a glycaemic trial involving healthy respondents (n=10). The present study demonstrated that noodles incorporated with CLP caused a signifcant (p<0.05) hypoglycaemic efect in the spike of postprandial blood glucose levels as compared to the control noodles (without CLP). Corresponding to the lowered postprandial glucose levels of CLP noodles, the glycaemic study conducted categorised the CLP noodles as a low glycaemic index (GI) food, as their GI scores were lower than 55 (CLP2.5=47, CLP5.0=43). In conclusion, the incorporation of CLP infuenced the glycaemic index of the noodles, shedding light on its potential as a functional ingredient for glycaemic management.